Crop Production Summary, Southeast Kansas – 2017 - G. F. Sassenrath; L. Mengarelli; J. Lingenfelser; X. Lin; D. E. Shoup (Kansas Agricultural Experiment Station Research Reports, 2018)
Crop production is dependent on many factors, most notably, environmental conditions during the growing season. Here, we summarize the environmental conditions during the 2017 growing season in comparison to previous years and the historical averages. Information on crop yields is taken from reported values and yields from variety trials in southeast and east central Kansas.
Keywords: crop production; corn; wheat; soybeans